Isolation and in silico prediction of potential drug-like compounds from Anethum sowa L. root extracts targeted towards cancer therapy. (February 2019) - Saleh-e-In, Md. Moshfekus; Roy, Ayan; Al-Mansur, Muhammad Abdullah; Mahmood Hasan, Choudhury; Rahim, Md. Matiur; Sultana, Nasim; Ahmed, Shamim; Islam, Md. Rabiul; van Staden, Johannes
Graphical abstract: Highlights: Anethum sowa L. has important spice and medicinal values for being used in culinary and pharmaceutical industries. Coumarins and anthraquinone compounds have been isolated in the roots part for the first time in this plant. Physcione and bergapten have been reported to be of immense significance from the aspect of cancer inhibition. Based on in silico studies, graveolone displayed promising anticancer potential with oncogenes of various cancer pathways. Abstract: Anethum sowa L. has been used as a spice herb in the Asian and European culinary systems to add flavour and taste. The studied plant has diverse folkloric medicinal value. Present study was designed to isolate phytochemicals from the hexane, chloroform and ethyl acetate extracts of the roots by various chromatographic techniques. Based on spectral analysis (IR, LC–MS, NMR) the isolated compounds were identified as physcione (1 ), β-sitosterol(2), stigmasterol(3), 2-oxo-3-propyl-2H-chromene-7-carboxylic acid (4 ), bergapten (5 ), 3-ethyl-7-hydroxy-2H-chromen-2-one (6 ) and graveolone (7 ). The mentioned compounds have been isolated for the first time from the roots part of the plant. Based on extensive literature review, physcione and bergapten were inferred to exhibit crucial bioactivities including inhibitory efficacy against various forms of cancer. Accordingly, in the present research approach molecular docking investigations of the isolated phytochemicals have been robustly executed with different oncogenes that have been reported to be actively involved in various forms of carcinoma. In silico investigations encompassing molecular docking analysis and drug-likeness profiling was executed to estimate the potential therapeutic tendencies of the phytochemicals targeted towards effective cancer therapy. Current investigation offers meaningful know-how pertaining to potential anticancer activities of the phytochemicals extracted from the roots of Anethum sowa L. and might open up new revenues towards effective drug development against cancer.